ESP-Based English Learning Model for Enhancing Financial Competence among Accounting Students: A Design-Based Research Study - Imam Suhaimi; Choirul Hana; Novy Anggraini Sudibyo (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to design, implement, and evaluate English learning models based on English for Specific Purposes (ESP) to enhance the competencies of finance students in accounting. A Design-Based Research (DBR) approach was employed to ensure the relevance and adaptability of the model through iterative refinement based on field feedback. Analysis of interviews and observations, conducted using thematic analysis, revealed that students experienced difficulties in understanding English terminology in finance, particularly in the contexts of reports, auditing, budgeting, and general financial communication. The developed learning model emphasizes module-based analysis of reports, financial statements, budget preparation, and audit scenarios, incorporating project-based activities that integrate professional skills, language, and contextual understanding. The model was implemented over one semester with 120 students from the Accounting Study Programs of three universities in East Java—Universitas Kahuripan Kediri, Universitas Pembangunan Nasional "Veteran" Surabaya, and Universitas Islam Malang—selected purposively to represent diverse academic and cultural learning contexts. Results indicate a significant improvement in students’ understanding of terminology, financial literacy, communication skills, and English-speaking ability. The statistical analysis showed a highly significant p-value (< .001) and a large effect size (d = 1.21), providing strong empirical evidence that the ESP-Accounting model effectively enhances integrated linguistic and financial competencies. This model can be adapted by other institutions to strengthen collaboration between lecturers and accounting professionals. Research in this area contributes to the advancement of language learning in educational and vocational contexts and enhances graduates’ readiness for the global workforce.